Westonci.ca offers quick and accurate answers to your questions. Join our community and get the insights you need today. Join our Q&A platform and connect with professionals ready to provide precise answers to your questions in various areas. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
To solve the system of equations:
[tex]\[ \begin{aligned} 2x + 8y &= 5 \quad \text{(Equation 1)} \\ 24x - 4y &= -15 \quad \text{(Equation 2)} \end{aligned} \][/tex]
We use the method of solving simultaneous equations. Here's the detailed step-by-step solution:
1. Rewrite equations if needed:
Equation 1: [tex]\( 2x + 8y = 5 \)[/tex]
Equation 2: [tex]\( 24x - 4y = -15 \)[/tex]
2. Simplify the equations:
If possible, simplify one or both of the equations. Since the coefficients of [tex]\( x \)[/tex] and [tex]\( y \)[/tex] are straightforward, we can proceed directly to elimination or substitution.
3. Elimination method:
Let's eliminate [tex]\( y \)[/tex]. To do this, we can first align the coefficients of [tex]\( y \)[/tex]. Notice the coefficients of [tex]\( y \)[/tex] are 8 (in Equation 1) and -4 (in Equation 2).
We can multiply Equation 1 by 1 to keep it unchanged:
[tex]\[ 1 \cdot (2x + 8y) = 5 \Rightarrow 2x + 8y = 5 \][/tex]
And we can multiply Equation 2 by 2 to make the coefficients of [tex]\( y \)[/tex] equal (but of opposite signs):
[tex]\[ 2 \cdot (24x - 4y) = 2 \cdot (-15) \Rightarrow 48x - 8y = -30 \][/tex]
4. Add the two equations to eliminate [tex]\( y \)[/tex]:
[tex]\[ \begin{aligned} (2x + 8y) + (48x - 8y) &= 5 + (-30) \\ (2x + 48x) + (8y - 8y) &= 5 - 30 \\ 50x + 0y &= -25 \\ 50x &= -25 \\ x &= -\frac{25}{50} \\ x &= -\frac{1}{2} \end{aligned} \][/tex]
5. Solve for [tex]\( y \)[/tex]:
Substitute [tex]\( x = -\frac{1}{2} \)[/tex] back into Equation 1 or Equation 2. We'll use Equation 1:
[tex]\[ 2x + 8y = 5 \][/tex]
Substitute [tex]\( x = -\frac{1}{2} \)[/tex]:
[tex]\[ 2\left(-\frac{1}{2}\right) + 8y = 5 \\ -1 + 8y = 5 \\ 8y = 6 \\ y = \frac{6}{8} \\ y = \frac{3}{4} \][/tex]
Therefore, the solution to the system of equations is:
[tex]\[ \left( -\frac{1}{2}, \frac{3}{4} \right) \][/tex]
Fill in the boxes with the solutions:
[tex]\[ \boxed{-\frac{1}{2}} \quad \boxed{\frac{3}{4}} \][/tex]
[tex]\[ \begin{aligned} 2x + 8y &= 5 \quad \text{(Equation 1)} \\ 24x - 4y &= -15 \quad \text{(Equation 2)} \end{aligned} \][/tex]
We use the method of solving simultaneous equations. Here's the detailed step-by-step solution:
1. Rewrite equations if needed:
Equation 1: [tex]\( 2x + 8y = 5 \)[/tex]
Equation 2: [tex]\( 24x - 4y = -15 \)[/tex]
2. Simplify the equations:
If possible, simplify one or both of the equations. Since the coefficients of [tex]\( x \)[/tex] and [tex]\( y \)[/tex] are straightforward, we can proceed directly to elimination or substitution.
3. Elimination method:
Let's eliminate [tex]\( y \)[/tex]. To do this, we can first align the coefficients of [tex]\( y \)[/tex]. Notice the coefficients of [tex]\( y \)[/tex] are 8 (in Equation 1) and -4 (in Equation 2).
We can multiply Equation 1 by 1 to keep it unchanged:
[tex]\[ 1 \cdot (2x + 8y) = 5 \Rightarrow 2x + 8y = 5 \][/tex]
And we can multiply Equation 2 by 2 to make the coefficients of [tex]\( y \)[/tex] equal (but of opposite signs):
[tex]\[ 2 \cdot (24x - 4y) = 2 \cdot (-15) \Rightarrow 48x - 8y = -30 \][/tex]
4. Add the two equations to eliminate [tex]\( y \)[/tex]:
[tex]\[ \begin{aligned} (2x + 8y) + (48x - 8y) &= 5 + (-30) \\ (2x + 48x) + (8y - 8y) &= 5 - 30 \\ 50x + 0y &= -25 \\ 50x &= -25 \\ x &= -\frac{25}{50} \\ x &= -\frac{1}{2} \end{aligned} \][/tex]
5. Solve for [tex]\( y \)[/tex]:
Substitute [tex]\( x = -\frac{1}{2} \)[/tex] back into Equation 1 or Equation 2. We'll use Equation 1:
[tex]\[ 2x + 8y = 5 \][/tex]
Substitute [tex]\( x = -\frac{1}{2} \)[/tex]:
[tex]\[ 2\left(-\frac{1}{2}\right) + 8y = 5 \\ -1 + 8y = 5 \\ 8y = 6 \\ y = \frac{6}{8} \\ y = \frac{3}{4} \][/tex]
Therefore, the solution to the system of equations is:
[tex]\[ \left( -\frac{1}{2}, \frac{3}{4} \right) \][/tex]
Fill in the boxes with the solutions:
[tex]\[ \boxed{-\frac{1}{2}} \quad \boxed{\frac{3}{4}} \][/tex]
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.